Policy Framework of the Free Nutritious Meal Program (MBG): Mapping Solutions to Reduce Plate Waste and Recover Value - Nur Mufida Wulan Sari; Gustaf Wijaya; Alqoma Subkhi (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background: The Free Nutritious Meal Program (MBG) is a government initiative enhancing the nutritional well-being of Indonesian children. However, significant plate food waste has emerged from public kitchens and schools. If not addressed, this waste could worsen the environmental crisis and impede the program's safety. The scale of food production in Nutrition Fulfillment units increases the potential for food waste to be generated. Objective: The study aims to find alternatives that reduce food waste in the MBG program. It also explores options to retain the economic value of the food waste produced by the MBG program. Research Methods/Implementation Methods: This research uses secondary data and a qualitative scoping review to explore literature on plate waste and economic value retention within the free nutritious meal program. Results: Multi-stakeholder efforts are needed to preserve both the economic and nutritional value of food waste. Through a circular economy approach and bioconversion technology, this waste can be converted into a productive resource. Evaluating the produced food menu can help reduce plate waste. This study supports food security, emission reduction, and local economic empowerment. Conclusion/Lesson Learned: The circular economy approach helps reduce waste, supports the government’s goal of better community nutrition, creates new economic opportunities from food waste, and strengthens environmental micro-enterprises.